Study of Exfoliated Molybdenum Disulfide (MoS2) - G, Munkhbayar; M, Otgonbaatar (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this study, We demonstrate mono and few layers MoS2 samples on the SiO2 (270nm)/Si substrate from bulk MoS2 crystal by micromechanical exfoliation technique. We also report that the Raman and PL intensity can be thermally modulated by annealing 1L, 2L and 7LMoS2 in a vacuum or air. We have systematically studied Atomic Force Microscopy, Raman and PL properties of mono and few layer MoS2 on the SiO2 (270nm)/Si substrate. First, we find that the number of layer values dependent the Raman and PL emission. First, Raman intensity area ratio of the MoS2 E12g, Ag1 and 2LA modes to that area of the Si substrate increased linear with increasing number of layers MoS2. Second, Normalized PL intensity area of the (A) peak decreased linear with increasing number of layers MoS2. The value of those graphs is a method to understand the number of layers the exfoliated MoS2. Third we found that some effects of the few layers MoS2after thermal annealed (vacuum and air 3000C for 40 min).